Examining the level of employee satisfaction with the performance of city managers (Case study: Baghershahr Municipality) - Jabbari, Shahnam; Jabbari, Behnam; Hanifapour, Mahin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: By referring to different organizations and taking a deep and expert look at the communication process in these organizations, this issue becomes apparent to every observer. One of the important and always noticeable problems in organizations that employees complain about is the lack of communication skills among their managers. One of the most important and key issues that has caught the attention of the body and the foundation of the organizational society in this period is the organizational commitment of the employees of an organization. This issue can have many factors and dimensions. The present study was conducted to investigate employee satisfaction with the performance of city managers of Baqershahr Municipality.Method: The statistical population of the research was all the employees of Baghershahr municipality, and Cochran's sample size formula was used to determine the sample size. Therefore, considering the error level of 0.05, the sample size was estimated to be 242 people. The data collection tool was a questionnaire. One-sample t-test, Pearson's correlation coefficient, multiple correlation and simultaneous multiple regression were used to analyze the data.Results: The results extracted from the above research emphasize the strong effect of job satisfaction on the commitment of the organization's employees. The managers of all levels of this municipality can know them better and more accurately and completely with the nobles and sufficient and accurate knowledge of the individual differences among their employees. As a result, taking actions that are most compatible with the heart desires of the employees increases their desire and motivation, satisfaction, and commitment in the direction of development and moving intelligently in the direction of the organization's goals. The level of satisfaction regarding the investigated components of job satisfaction is average, managers are high, and for the components related to welfare, it is below 40%.Conclusion: The results show that municipal employees have low and very low satisfaction with the amenities in the municipality.